PENGARUH LEBAR PONDASI TERHADAP KEDALAMAN MUKA AIR TANAH DI BAWAH DASAR PONDASI DALAM MENENTUKAN BESARNYA DAYA DUKUNG ULTIMIT DAN DAYA DUKUNG AMAN PONDASI MENERUS PADA TANAH LUNAK DENGAN METODE TERZAGHI PADA KONDISI KERUNTUHAN GESER LOKAL - Fitria Handayani (Universitas Lambung Mangkurat, 2021)
The foundation is the lowest part of the building that continues the load force into the soil or rocks in the soil. Longitudinal foundations are foundations that support elongated walls and rows of closely spaced columns so that if you use a footed foundation, the sides coincide. The design of the foundation must meet the requirements of the safety factor with a value of more than equal to three and the settlement of the foundation is within the tolerance limit. Long-term stability of the foundation must pay attention to the location of the base of the foundation in order to reduce the risk of swelling and shrinkage of the soil, erosion of the foundation surface, scouring on the foundation walls and other soil disturbances. The method used in this study is the terzaghi method because the soil layer is homogeneous and the internal friction angle is < 29o. The ultimate bearing capacity of Terzaghi is used to calculate the bearing capacity of granular soils and soils that have internal friction angle values (Ø) and cohesion (c). The depth of the groundwater table from the base of the foundation greatly affects the ultimate bearing capacity and the safe bearing capacity of the foundation. The further away the groundwater table is from the base of the foundation, the greater the value of the ultimate bearing capacity of the foundation (qu) causing the higher value of the foundation's safe bearing capacity (qs). This study analyzes local shear failure with the highest ultimate bearing capacity of 173.36 t/m2 and the largest safe bearing capacity of 59.56 t/m2 occurs when the depth of the groundwater table is greater than the width of the foundation, while the lowest ultimate bearing capacity is 170.72 t/m2. m2 and the lowest safe bearing capacity of 58.68 t/m2 occurs when the water level is at the base of the foundation.